2001
DOI: 10.1055/s-2001-16213
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Treatment for Laterally Spreading Tumors in the Colon

Abstract: When LSTs meet the above endoscopic criteria, EMR should be the first-line treatment because of the low risk of massive submucosal invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(144 citation statements)
references
References 5 publications
5
138
1
Order By: Relevance
“…Matsuda et al [29] , Watari et al [33] , 1998 Snare 186 Lateral spreading tumor EMR 12 Sugisaka et al [34] , 2003 Snare 162 No information EMR 13 Matsunaga et al [35] , 1999 Snare 134 No information EMR 14 Nomura et al [36] , 2001 Snare 54 No information EMR 15 Kobayashi et al [37] , 1999 Snare 131 No information EMR 16 Nakajima et al [38] , 2006 Snare 52 No information EMR 17 Cho et al [39] , 1999 Snare 34 No information EMR 18 Saito et al [40] , 2001 Snare 170 Lateral spreading tumor EMR 19 Tanaka et al [13] , 2001 Snare with needle spike 81 Lateral spreading tumor EMR 20 Ahmad et al [41] , 2002 Snare with suction 41 Colon and rectum EMR 21 Hurlstone et al [42] , to be between 7% and 34% for large sessile polyps [6,48] . Further more, our meta-analysis revealed that experience performing EMR plays an important role in achieving a better en-bloc resection and cure en-bloc tumorfree rate.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuda et al [29] , Watari et al [33] , 1998 Snare 186 Lateral spreading tumor EMR 12 Sugisaka et al [34] , 2003 Snare 162 No information EMR 13 Matsunaga et al [35] , 1999 Snare 134 No information EMR 14 Nomura et al [36] , 2001 Snare 54 No information EMR 15 Kobayashi et al [37] , 1999 Snare 131 No information EMR 16 Nakajima et al [38] , 2006 Snare 52 No information EMR 17 Cho et al [39] , 1999 Snare 34 No information EMR 18 Saito et al [40] , 2001 Snare 170 Lateral spreading tumor EMR 19 Tanaka et al [13] , 2001 Snare with needle spike 81 Lateral spreading tumor EMR 20 Ahmad et al [41] , 2002 Snare with suction 41 Colon and rectum EMR 21 Hurlstone et al [42] , to be between 7% and 34% for large sessile polyps [6,48] . Further more, our meta-analysis revealed that experience performing EMR plays an important role in achieving a better en-bloc resection and cure en-bloc tumorfree rate.…”
Section: Discussionmentioning
confidence: 99%
“…Polypectomy is normally indicated for pedunculated or adenomatous semi-pedunculated polyps, while EMR is suitable for sessile, semi-pedunculated, or superficial tumors that are likely to be carcinoma [6,57]. ESD allows complete en bloc resection regardless of the size of the lesion [28,31,58,59]. Colorectal ESD is thus indicated for lesions requiring endoscopic en bloc resection when it is difficult to use the snare technique [31].…”
Section: Commentmentioning
confidence: 99%
“…Most LST-Gs are considered adenomatous lesions. Among homogenous-type LST-Gs, the incidence of carcinoma or submucosal invasion is extremely low [28,29]. Large nodule in a nodular mixedtype LST-G, where submucosal invasion tends to be present [30], should be resected en bloc [31].…”
Section: Cq What Therapy Is Indicated For Laterally Spreading Tumorsmentioning
confidence: 99%
“…For en bloc resection of flat lesions larger than 20 mm, conventional EMR is inadequate because of incomplete removal and frequent local recurrence. When analyzing the endoscopic features of 257 LSTs in order to assess which features correlated with the depth of invasion, unevenness of nodules, presence of large nodules, size, histological type, and presence of depression in the tumor were significantly associated with the depth of invasion [41] . In addition, LST-NG showed a higher frequency of sm invasion than LST-G (14% vs 7%) [42] .…”
Section: Endoscopic Resection Of Colorectal Tumorsmentioning
confidence: 99%
“…This supports the therapeutic effectiveness of endoscopic removal of polyps and flat lesions that are confined to the mucosa, regardless of their size. On the other hand, colorectal laterally spreading tumor (LST) classified as granular (LST-G) and non granular type (LST-NG), are defined as lesions larger than 10 mm in diameter, with a low vertical axis, extending along the luminal wall [41] . For en bloc resection of flat lesions larger than 20 mm, conventional EMR is inadequate because of incomplete removal and frequent local recurrence.…”
Section: Endoscopic Resection Of Colorectal Tumorsmentioning
confidence: 99%